Designing a mobile user experience student knowledge management system using Lean UX - Condro Kartiko; Hesa Abda Arrasyid; Ariq Cahya Wardhana (Journal of Engineering and Applied Technology, 2021)
Student Affairs at Telkom Purwokerto Institute of Technology has a lot of information and knowledge that all students need to know. However, this information and knowledge have not been maximally conveyed to students. Student affairs have a scope of work to handle the Student Creativity Program (PKM), Student Organization (Ormawa), scholarships, Student Activity Transcripts (TAK), and lectures. Therefore, one of the efforts to facilitate Student Affairs in conveying various knowledge is a Student Knowledge Management System mobile application. User Experience student KMS mobile application designed for mobile devices that focus on interface design. The development of this application interface uses the Lean UX method. The Lean UX method has four stages: Declare Assumptions, Create an MVP, Run an Experiment, and Feedback and Research. The application design is evaluated using the Enhanced Cognitive Walkthrough (ECW) to produce a prototype of a knowledge management system or Knowledge Management System for IT Telkom Purwokerto student affairs according to the user's wishes. The test results show success in all tasks, so it can be concluded that the application design has achieved a good user experience.